Konsep akhlak dalam Tafsir Al-Ibriz: Analisis hermeneutika terhadap penafsiran KH. Bisri Musthofa atas QS. Luqman ayat 13–19 - vidhania, Aiska rahma (Maliki Interdisciplinary Journal, 2026)
Surah Luqman verses 13–19 are widely recognized for their emphasis on moral education through the heartfelt advice of Luqman to his son. These verses highlight core ethical teachings, including the affirmation of God’s oneness, devotion to parents, the importance of prayer, kindness toward others, and the avoidance of arrogance. When interpreted through Tafsir al-Ibriz by KH. Bisri Musthofa, these values are presented in simple and accessible language that resonates with Javanese cultural nuances, reflecting a localized and grounded style of Qur’anic interpretation. This study examines the concept of akhlāq in Surah Luqman verses 13–19 based on the explanations found in Tafsir al-Ibriz. The commentary interprets these verses using clear, community-friendly language while showcasing a local interpretive character rooted in Javanese socio-cultural values. Using a library research method and a hermeneutical approach, this study explores the moral messages conveyed in the verses. The findings indicate that the concept of akhlāq in Tafsir al-Ibriz does not merely emphasize individual ethics but also contains social messages relevant to modern life, such as maintaining good relations, avoiding arrogance, and grounding every aspect of life in strong monotheistic values.